Optimizing Indonesian Language Learning Evaluation Management to Enhance Student Learning Outcomes - Rizki Fitriani; Ade Rahmad Kurniawan; Aan Budianto (Journal of Educational Management Research, 2026)
Learning evaluation management is a critical component in ensuring the achievement of Indonesian language learning objectives in higher education. This study aims to analyze the optimization of learning evaluation management at ITS NU Lampung using the POAC (Planning, Organizing, Actuating, Controlling) approach and the CIPP (Context, Input, Process, Product) evaluation model to gain a comprehensive understanding of evaluation effectiveness and its contribution to improving student learning outcomes. A qualitative approach was employed, with data collected through interviews, observations, and documentation, and analyzed through data reduction, presentation, and conclusion drawing, involving lecturers and students enrolled in the Indonesian Language course. The findings indicate that, based on the POAC approach, evaluation planning has not been grounded in needs analysis, organizational arrangements lack institutional standards, implementation remains focused on cognitive aspects, and supervision lacks quality control mechanisms. Using the CIPP model, it was found that context analysis is insufficient, input utilization is suboptimal, the evaluation process tends to be conventional, and evaluation results have not been used as a basis for continuous improvement. The study highlights the need for a more systematic and coordinated evaluation management, including the implementation of standardized assessment instruments, enhancement of authentic assessment, and provision of formative feedback, to improve the effectiveness of learning and student outcomes